2012
DOI: 10.1111/j.1748-5967.2012.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the dung beetle, Copris tripartitus (Coleoptera: Scarabaeidae), that is endangered in Korea

Abstract: The dung beetle, Copris tripartitus (Coleoptera: Scarabaeidae), is an endangered insect in Korea. In order to establish a conservation strategy, a preliminary investigation on the genetic diversity of Korean populations was performed using mitochondrial COI (658 bp), CytB (433 bp), and nuclear ITS2 (411 nucleotide positions). Sequencing of 69 individuals collected from five localities showed substantially higher variability (5.02% for COI, 4.62% for CytB, and 8.03% for ITS2). The resulting networks for mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…It was difficult to find comparable data obtained under similar experimental conditions. Several previous studies have reported the magnitude of genetic diversity of several insect species found in South Korea using partial COI gene sequences (e.g., Kang et al, 2012). When these results were considered, the maximum sequence divergence of the COI gene in An.…”
Section: Overall Low Mtdna Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was difficult to find comparable data obtained under similar experimental conditions. Several previous studies have reported the magnitude of genetic diversity of several insect species found in South Korea using partial COI gene sequences (e.g., Kang et al, 2012). When these results were considered, the maximum sequence divergence of the COI gene in An.…”
Section: Overall Low Mtdna Diversitymentioning
confidence: 99%
“…yamamai (0.46%, 3 bp) was one of the lower ones. The others ranged from 0.15 (pear psylla in Hemiptera; Kang et al, 2012) to 11.0% (oriental mole cricket in Orthoptera; Kim et al, 2007). Similarly, the h of An.…”
Section: Overall Low Mtdna Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Endangered insect species in South Korea, tiny dragonfly ( Nonnophya pygmaea ) and dung beetle ( Copris tripartitus ), exhibited different genetic diversity aspects. Copris tripartitus showed relatively high haplotype diversity (0.962–1.000) and nucleotide diversity (0.011–0.022) (Kim et al ), whereas N. pygmaea showed relatively low haplotype diversity (0.0–0.8444) and nucleotide diversity (0.0–0.0026) (Kang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Oh and co-workers chemically investigated a diverse population of Actinobacteria from the indigenous soil-dwelling Korean dung beetle ( Copris tripartitus ), its larvae and dung balls [ 102 103 ]. Dung beetles are prime contributors to the cyclic breakdown of organic waste material, and their life cycle is tightly dependent on herbivore faeces [ 104 – 105 ]. Based on unique metabolomic profiles (UV chromatogram) and HRMS data, several of the isolated Streptomyces strains were selected for large scale fermentation.…”
Section: Reviewmentioning
confidence: 99%